2010
DOI: 10.1176/appi.ajp.2009.09070977
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders in Preschool Offspring of Parents With Bipolar Disorder: The Pittsburgh Bipolar Offspring Study (BIOS)

Abstract: Objective-To evaluate lifetime prevalence and specificity of DSM-IV psychiatric disorders and severity of depressive and manic symptoms at intake in preschool offspring of parents with Disorder I-II.Methods-121 offspring ages 2-5 years old of 83 parents with Bipolar Disorder and 102 offspring of 65 demographically matched control parents (29 with non-Bipolar psychiatric disorders and 36 without any lifetime psychopathology) were recruited. Parents with Bipolar Disorder were recruited through advertisement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
3
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 73 publications
(71 reference statements)
6
108
3
15
Order By: Relevance
“…More recently, two review articles on bipolar offspring reported elevated but varying prevalence rates of bipolar disorder (ranging from 3% to 27%), mood disorders (ranging from 5% to 67%), and non-mood disorders (ranging from 5% to 52%) (2,3). However, these studies could not fully address the development and early course of bipolar disorder and other mood disorders because they used either a crosssectional design or a longitudinal design without follow-up into adulthood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We report here on one of the largest prospective bipolar offspring studies with a follow-up into adulthood: the 12-year follow-up of the Dutch bipolar offspring cohort (7,10,12).…”
mentioning
confidence: 99%
“…More recently, two review articles on bipolar offspring reported elevated but varying prevalence rates of bipolar disorder (ranging from 3% to 27%), mood disorders (ranging from 5% to 67%), and non-mood disorders (ranging from 5% to 52%) (2,3). However, these studies could not fully address the development and early course of bipolar disorder and other mood disorders because they used either a crosssectional design or a longitudinal design without follow-up into adulthood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We report here on one of the largest prospective bipolar offspring studies with a follow-up into adulthood: the 12-year follow-up of the Dutch bipolar offspring cohort (7,10,12).…”
mentioning
confidence: 99%
“…Este hallazgo es interesante debido a que, a pesar de que la muestra total de niños y adolescentes fue obtenida de la comunidad, en el presente estudio la frecuencia de trastornos externalizados en hijos de padres con TBP fue casi 15 veces más alta que la reportada en otros estudios con población general 23 y casi 50 veces más alta que la reportada en la encuesta nacional de adolescentes. 24 Los resultados también son consistentes con otros estudios internacionales que reportan tasas elevadas de trastornos de conducta disruptiva y TDAH en los hijos de padres con TBP cuando se comparan con hijos de padres sanos 19 y/o con otra psicopatología diferente al TBP.…”
Section: Resultados Características Sociodemográficasunclassified
“…10 Cuando consideramos la perspectiva del desarrollo, los estudios realizados en preescolares reportan una prevalencia ocho veces mayor para la presencia de TDAH, así como mayor frecuencia de síntomas depresivos y maniacos subumbrales, en comparación con los hijos de padres sin TBP. 19 En la adolescencia se observa un incremento en la prevalencia del diagnóstico de TBP (de 3 a 10%) y en mayor proporción para cualquier trastorno del ánimo (40%). 20 El estudio de esta población es interesante debido a las necesidades de atención, disfunción y psicopatología temprana que influyen, en una trayectoria heterotípica, en otros trastornos crónicos y discapacitantes.…”
unclassified
“…47 There are often differences in the sampling or recruitment strategy employed (clinical/community; offspring of one affected parent/two affected parents), the assessments used (self/observer-rated), and the timeframe of assessment (cross-sectional/longitudinal; retrospective/prospective). The methods employed to recruit families into OSBP studies also vary widely, and include recruitment of families already involved in neurobiological and genetic research projects, 48 recruitment of all or some participants via selfreferral and/or advertising campaigns, 49 recruitment from hospital settings and specialized clinics, 50 and from patient advocacy associations. 44 Notably, higher rates of comorbidity are evident in studies that recruit via selfreferral and families where the non-proband parent also had a non-affective psychiatric illness.…”
Section: Clinical Presentation Of Early Stagesmentioning
confidence: 99%